2015
DOI: 10.1152/ajprenal.00537.2014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress contributes to orthopedic trauma-induced acute kidney injury in obese rats

Abstract: After trauma, obese patients have an increased risk of developing acute kidney injury (AKI). We have demonstrated that obese Zucker (OZ) rats, but not lean Zucker (LZ) rats, develop AKI 24 h after orthopedic trauma. ROS have been implicated in the pathophysiology of AKI in models of critical illness. However, the contribution of ROS to trauma-induced AKI in the setting of obesity has not been determined. We hypothesized that AKI in OZ rats after trauma is mediated by increased oxidative stress. Male LZ and OZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 59 publications
(1 reference statement)
2
23
0
2
Order By: Relevance
“…Reactive oxygen species play an important role in mediating innate immune responses, including activation of damage-associated molecular pattern molecules, neutrophil priming, stimulation of oxidant-related transcription factors and molecular events, and production of cytokines and chemokines. Interestingly, we found that antioxidant treatment decreases lung neutrophil numbers, myeloperoxidase activity, and plasma interleukin-6 levels in obese Zucker rats following trauma, suggesting that exacerbated oxidative stress in obesity facilitates or exaggerates immune responses (58, 96). In addition, we found that the pulmonary microvasculature in obese Zucker rats exhibit increased basal permeability and is more vulnerable to elevated oxidative stress as compared to lean Zucker rats (58, 96).…”
Section: Obesity and Animal Models Of Critical Illnessmentioning
confidence: 85%
See 2 more Smart Citations
“…Reactive oxygen species play an important role in mediating innate immune responses, including activation of damage-associated molecular pattern molecules, neutrophil priming, stimulation of oxidant-related transcription factors and molecular events, and production of cytokines and chemokines. Interestingly, we found that antioxidant treatment decreases lung neutrophil numbers, myeloperoxidase activity, and plasma interleukin-6 levels in obese Zucker rats following trauma, suggesting that exacerbated oxidative stress in obesity facilitates or exaggerates immune responses (58, 96). In addition, we found that the pulmonary microvasculature in obese Zucker rats exhibit increased basal permeability and is more vulnerable to elevated oxidative stress as compared to lean Zucker rats (58, 96).…”
Section: Obesity and Animal Models Of Critical Illnessmentioning
confidence: 85%
“…Additionally, we observed significant increases in systemic, lung, and renal inflammation and oxidative stress the day after trauma in obese rats, and the inhibition of NADPH oxidase (NOX), a major source of superoxide, prevented the development of both lung and kidney injury in the obese Zucker rats but had no effect in lean rats (58, 96). These results suggest that trauma increases the incidence of kidney and lung injury in obesity due, at least in part, to exacerbated oxidative stress.…”
Section: Obesity and Animal Models Of Critical Illnessmentioning
confidence: 89%
See 1 more Smart Citation
“…[25][26][27] In post-traumatic AKI in obese rats, SOD activity was reported to be suppressed. 28 It has been reported that in AKI patients, the NADPH oxidase p22phox gene polymorphism was associated with dialysis requirements and death. 29 In our study, it was similarly determined that gene polymorphism of CAT, an antioxidant enzyme, was also related to intensive care requirements and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Large recent studies indicate that obese patients have an increased mortality risk following trauma (3), so it would be interesting to compare differences between outcomes in trauma versus other critically ill patients who are obese, as these demographics would likely have disparate malnutrition profiles as well as a different burden of comorbid conditions. We have recently shown that following orthopedic trauma, obese rats have an increased risk of developing acute lung and kidney injury, and that these are mediated by exacerbated hyperglycemic, inflammatory, and oxidative stress responses in obese as compared to nonobese rodents (4, 5). Clinical studies have shown that these variables are also associated with poor outcomes in the critically ill.…”
mentioning
confidence: 99%